All Questions Topic List
Integration Questions
Previous in All Question Next in All Question
Previous in Integration Next in Integration
Question Number 32031 by abdo imad last updated on 18/Mar/18
letf(a)=∫0∞e−axln(x)dxwitha>0 1)findf(a) 2)find∫0∞e−ax(xlnx)dx 3)calculate∫0∞e−2x(xlnx)dx.
Commented byabdo imad last updated on 20/Mar/18
ch.ax=tgivef(a)=∫0∞e−tln(ta)dta =1a∫0∞e−t(ln(t)−ln(a))dt =1a∫0∞e−tln(t)dt−ln(a)a∫0∞e−tdtbutwehaveproved that∫0∞e−tln(t)dt=−γ⇒f(a)=−γa−ln(a)a 2)wehavef′(a)=−∫0∞xe−axln(x)dx⇒ ∫0∞e−ax(xln(x))dx=−f′(a)fromanotherside f′(a)=γa2−1−ln(a)a2=γ+ln(a)−1a2⇒ ∫0∞e−ax(xlnx)dx=1−γ−ln(a)a2 3)fromrel.2)lettakea=2weget ∫0∞e−2x(xln(x))dx=1−γ−ln(2)4.
Terms of Service
Privacy Policy
Contact: info@tinkutara.com